Leak-Testing of an Endoscopic Aerosol Box for Preventing SARS-CoV-2 Infection during Upper Gastrointestinal Endoscopy - Kitiyakara, Taya; Kamalaporn, Patarapong; Poolsombat, Akharawit; Anumas, Patthama; T. Tawarate, Thanyaluck; Akkanit, Kesrada (Siriraj Medical Journal, 2021)
Objective: The SARS-CoV-2 virus has infected many healthcare professionals. Endoscopy is an aerosol-generating procedure and the endoscopy team is at risk of exposure and infection. We describe the leak-testing of an aerosol box that uses a glove-covering for the endoscope. Materials and Methods: An endoscopic aerosol box with a glove-covering over the endoscope was made for gastroscopy, EUS and ERCP procedures and was tested for leakage of aerosol/airborne particles. Fine particulate matter (PM) from burnt incense sticks was used as a model for viral aerosol. The leakage from the box was measured by comparing readings from 2 PM light-scattering sensors, one placed inside the box and the other just outside the glove opening in a sealed container. Negative pressure conditions were also used to see if this had any effect on the leakage. Results: The concentration levels of the particulate matter differed with different negative pressure conditions and movement of the endoscope through the glove. Very little leakage was seen with the endoscope stationary even with no negative pressure, at 2.4%, 0.17% and 0.07% for PM1, PM2.5 and PM10, respectively. The maximum leakage was 14% for PM1, 8.7% for PM2.5 and 2.6% for PM10 in the moving-endoscope condition and no negative pressure. This reduced to 6.2%, 1.3%and 0.37% respectively when suction was applied at full strength (negative pressure of -0.05 bar). Conclusion: The glove covering significantly reduced the passage of particles. The particulate leak was seen most with the smallest particles and reached 14% for PM1 without negative pressure. This reduced to 6.2% with maximum negative pressure using the wall suction.